Chinese Students Wary of Studying in the United States - Wan, Xiaofeng (International Higher Education, 2020)
In a recent survey, 87 percent of high school college counselors in China said that their students and parents are now reconsidering plans for studying in the United States. Eighty-five percent among them attributed this new trend to Trump’s hostile rhetoric and unpredictable policies toward Chinese students. This has pushed Chinese students to look elsewhere for alternatives, directly benefiting competitor countries. Despite the pessimistic outlook, the United States still remains a prime destination for many Chinese students, particularly its top-tier institutions.